Kontribusi Gratitude Dan Anxiety Terhadap Spiritual Well-Being Pada Orang Tua Anak Berkebutuhan Khusus - Meiza, Asti; Puspasari, Diah; Kardinah, N (HUMANITAS, 2018)
This research aims to determine the effect Gratitude and Anxiety with Spiritual Well-Being to the special needs’s parents. The population of special needs increase in the last decade. Research carried out by the quantitative method with 100 subjects. Data analysis was performed using multiple linear regression model where Gratitude and Anxiety as independent variables and Spiritual Well Being (SWB) as the dependent variable. Results of the first study is the correlation coefficient between independent variables and the dependent variable is 0.679. Multiple Linear Regression Model obtained was Y = 23.757 + 0,798X1 + 0,308X2. These results indicate a positive influence between Gratitude and Anxiety to SWB. According to the theory, Anxiety should contribute negatively to SWB. Allegedly this is because the majority of the subjects had State Anxiety, so they can manage and control the emotions that give a positive effect on SWB.